INDEPENDENT CURRICULUM ASSESSMENT AT MA NEGERI 2 PONTIANAK - Iwan Ramadhan (Sean Institute, 2023)
This research aims to determine the assessment of the independent curriculum at MAN 2 Pontianak. The independent curriculum assessment has a series of assessments that are different from the 2013 curriculum. Therefore, long before schools implement the independent curriculum, teaching staff have been provided with knowledge and experience. This research method is a descriptive qualitative type. Data was collected through observation and interviews. The analysis was carried out according to the Milles and Huberment analysis. The results of this research are assessments carried out at MAN 2 Pontianak on intracurricular and co-curricular activities. The Pancasila Student Profile Project is a formative and summative assessment activity. In these activities, students explore, interpret, synthesize and produce products from learning outcomes. Then, during that time, the teacher also carries out assessments to measure the achievement of learning objectives and reflect on future learning activities. The obstacle faced is teachers who focus too much on theory and do not use an approach to using technology. Meanwhile, students still have a conventional learning mindset. MAN 2 Pontianak students were more proactive and creative during the assessment. Thus, the differences in independent curriculum assessment provide significant changes in achieving learning objectives and teacher reflection on the learning process.